Validation of performance of Spanish version of PURE-4 questionnaire for early identification of psoriatic arthritis after 1 year of follow-up in patients with psoriasis - R. Queiro-Silva; A. López-Ferrer; M. Ferran i Farrés; R. Rivera-Díaz; D. Vidal-Sarro; L. Rodríguez Fernández-Freire; P. de la Cueva-Dobao; J. Santos-Juanes; V. Rocamora-Duran; L. Gómez-Labrador; I. Belinchón-Romero (PLoS ONE, 2026)
Background and objective Psoriatic arthritis (PsA) is an inflammatory, chronic and progressive musculoskeletal disease associated with psoriasis. The validation of the Spanish version of the Psoriatic arthritis UnclutteRed screening Evaluation (PURE-4) questionnaire has been published previously. The present analysis studied the performance of the PURE-4 questionnaire for the early detection of PsA one year before its diagnosis. Materials and methods This was an observational multicenter study, including two cross-sectional assessments, with primary data collection in routine clinical practice in Spain. Adult patients with psoriasis and confirmed not having PsA diagnosis during Assessment I completed Assessment II by the rheumatologist one year (±2 months) after answering the PURE-4 questionnaire. This work presents the results of Assessment II, to confirm/rule out the presence of PsA in patients with psoriasis one year after PURE-4 answering. The analysis, involving the results from Assessment II, will evaluate the performance of the PURE-4 questionnaire for the early detection of potential PsA in terms of sensitivity and specificity. Results There were 219 evaluable patients, 56.2% male, and the mean (standard deviation [SD]) age was 46.8 (12.5) years. At one year, the PsA diagnosis was confirmed in 12 (5.5%) patients, representing 26.1% of the total number of patients with PsA diagnosed since the beginning of the study. The mean (SD) PURE-4 score was 2.4 (1.1) for patients with PsA and 1.2 (1.2) for patients without a diagnosis of PsA (p = 0.0016). The area under the receiver-operating characteristic (ROC) curve confirmed the good quality of the questionnaire (0.7618; 95% CI: 0.6530–0.8706; n = 217). PURE-4 showed a sensitivity of 75.0% and a specificity of 62.9%. Conclusions The PURE-4 questionnaire offers good clinimetric capabilities for the early detection of PsA with a score ≥2. Of the total number of patients with PsA, one in four were detected one year after answering positively to the questionnaire, which would help to predict which patients are at high risk of developing PsA. The authors reinforce the recommendation to closely follow up with these patients.